Design estratégico educacional, as competências para o futuro e as articulações dos regimes de interação, sentido e risco: uma educação para a trabalhabilidade - Gonçalves, Letícia Pedreira Diniz (2022)
The present research sought to investigate the relationship between the skills developed by private institutions of higher education in Brazil and the world of work in the Information Age. It starts from the assertion that education adopts a strategic design that reproduces the educational model disconnected from current demands. For this, it considers investigating the intertwined relationship between education and professional development, especially higher education. To achieve the objective, we sought to understand the development of matrix dimensions such as: the discipline grid, the teaching-learning methodologies, the locus, the profile of the faculty, the profile of the graduate, the extracurricular activities and the interactions with the professional market to analyze the factors that impact the adequacy between 'what is expected by the job market' and 'what is taught to enter the professional market'. It considers, therefore, that the world of work can contemplate educational models aimed at employability, but also at workability, since the market allows the exercise of new careers. To investigate the context of competences for the future with a focus on workability, it researches reference documents such as the reports of the World Economic Forum (2020) and the DCNs of the Ministry of Education. To conduct the research, a single case study was adopted as a corpus: Faculdade Sebrae. This adopted a matrix based on entrepreneurial education comprising technical skills and emotional intelligence with a focus on entrepreneurship and skills for the future. The tested hypotheses use a qualitative approach and include the twenty-four students from the second and third classes as a sample. The exploratory field research used participant observation and the application of a semi-structured questionnaire to analyze, in the light of discursive semiotics, the proposed educational design, given the articulations of the regimes of interaction and meaning (Landowski, 2014) and the educational relationship (Landowski, 2016). As a result of the thesis, it was possible to note the importance of articulating risk regimes to deal with skills and the workability market of the future. In order for strategic design to focus on the connection between teachers and students, it is necessary to make the regimes of meaning and interaction more complex, enabling dimensions that allow transitions between founding principles and correlated attitudes. The research pointed out that education that does not only focus on the employability market, must consider practical learning spaces that are able to exchange between the subjects of interaction, teachers with challenging and participatory attitudes. The variable transmitted by the teachers and best evaluated was the 'ability to identify problems'. For this, simulations, games and group activities were pointed out as indicated methodologies. Among the Entrecomp competencies (2016), ‘dealing with uncertainty’ was listed as the most important to start a business of your own. But when the survey asked about 'getting and choosing a job', 'being selfaware' was the most cited variable. Furthermore, the tracks specifically developed, Entrepreneurship and Future Skills, were identified as those that correlate theory and practice